Clinical efficacy of resin-based direct posterior restorations and glass-ionomer restorations – An updated meta-analysis of clinical outcome parameters. Issue 5 (May 2022) - Heintze, Siegward D.; Loguercio, Alessandro D.; Hanzen, Taíse A.; Reis, Alessandra; Rousson, Valentin
Abstract: Objective: The present review is an update of a systematic review that has been published in 2012. Meanwhile, many new clinical trials on resin composites had been published. New materials such as bulk fill resin composites and new glass-ionomer (GIC) based materials had been introduced. The focus of this review was to evaluate the longevity in relation to the material class and adhesive class, while adjusting for a possible study bias effect. Material and methods: The database PUBMED/SCOPUS were searched for clinical trials on posterior resin composites. The inclusion criteria were: (1) studies published between 2000 and 2019, (2) prospective clinical trial with at least 2 years of observation; (2) minimal number of restorations at last recall = 20; (3) report on drop-out rate; (4) report of operative technique and used materials; (5) utilisation of Ryge, modified Ryge or FDI evaluation criteria. The bias of each study was assessed by two independent reviewers using Cochrane Collaboration's tool for assessing risk of bias in randomised trials. For the statistical analysis, linear mixed models fitted on the individual data recorded along time have been used with random effects to account for study, patients and experiment effects. P-values smaller than 0.05 were considered significant. Results: Of the 423 clinical trials, 62 studies (including 110 experiments) met the inclusion criteria. Material class was divided according to the composite filler in microhybrid (39 experiments/2807 restorations), nanohybrid (24 experiments/1254 restorations), and hybrid (22 experiments/1255 restorations). So-called bulk fill materials were treated as a separate category (9 experiments/506 restorations) as were the GIC (11 experiments/2121 restorations) and the compomer materials (5 experiments/238 restorations). Only one study (1.6%) had low risk of bias, 42 (67.7%) were assessed to have unclear risk of bias and 19 (30.6%) had a high risk of bias. In 52.3% of the studies Class II and Class I restorations had been placed. After 10 years, the survival rate for resin composite restorations dropped to about 85–90% with no significant difference between hybrid, microhybrid and nao-hybrid resin materials. The main reasons for restoration replacement were bulk fractures and wear, which accounted for a about 70% of replacements. Caries at the restorative margins accounted for about 20% of the replacements, and retention loss, inacceptable colour match or marginal integrity, endodontic treatment or cusp fracture for about 10% of the replacements of the resin composite restorations. For compomer and GIC restorations the mean overall survival rate was about 80% after 6 years. For GIC, the main reasons for failure were substantial loss of anatomical contour along with loss of proximal contacts and retention loss. Mainly fractures reduced the longevity of compomers restorations. Also, there was no statistically significant difference between hybrid, micro-hybrid, nano-hybrid and bulk fill resin composites with regard to colour match, surface texture, material fractures, and anatomical form. Conclusions: Posterior resin composite restorations that were placed with the enamel etch technique showed the best overall performance; the longevity was not significantly influenced by the filler type or viscosity of resin composite material. With regard to colour match, surface texture and anatomical form, nanohybrid resins were not significantly superior to hybrid or microhybrid resin composites. Compomer and GIC restorations demonstrated considerable shortcomings and had a significant shorter longevity.